2014
DOI: 10.1111/ejh.12434
|View full text |Cite
|
Sign up to set email alerts
|

LDH is an adverse prognostic factor independent of ISS in transplant‐eligible myeloma patients receiving bortezomib‐based induction regimens

Abstract: In this uniformly treated cohort of transplant-eligible myeloma patients, elevated serum LDH is an adverse risk factor independent of ISS for both OS and EFS. Bortezomib-based induction/ASCT regimen had not abolished the adverse impact of elevated LDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
2
15
0
1
Order By: Relevance
“…Previous studies confirmed that LDH is an adverse prognostic factor for myeloma. Chim et al 24 reported that LDH is an adverse prognostic factor independent of ISS in transplant-eligible myeloma patients receiving bortezomib-based induction regimens. Moreover, multivariate analysis including LDH, ISS stage, etc showed that ISS stage was no longer an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies confirmed that LDH is an adverse prognostic factor for myeloma. Chim et al 24 reported that LDH is an adverse prognostic factor independent of ISS in transplant-eligible myeloma patients receiving bortezomib-based induction regimens. Moreover, multivariate analysis including LDH, ISS stage, etc showed that ISS stage was no longer an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirm that patients with LCMM have poorer outcome than other MM subtypes, in terms of OS. This worse prognosis is justified, to a certain point, by the association of LCMM with several established negative prognostic factors such as ISS III [6], renal failure [7], male sex [8], high LDH levels [9] and high FLCr i/u [10]. After adjustment for key prognostic factors, LCMM remains an independent factor associated with OS.…”
Section: Discussionmentioning
confidence: 99%
“…Based on analysis of multiple clinico‐pathological risk factors in 2031 patients with diffuse large B cell lymphoma treated by anthracycline‐containing regimens, elevated LDH is one of the five factors (age, stage, LDH, performance status, number of extranodal sites) prognostic of survival in the International Prognostic Index (Shipp et al , ). Similarly, elevated LDH was also found to be an important adverse prognostic factor in multiple myeloma by Barlogie et al (), and subsequently verified in other studies (Chim et al , ; Palumbo et al , ), Indeed, elevated LDH, in addition to high‐risk fluorescence in situ hybridisation (FISH) aberration, was incorporated into the Revised International Staging System (ISS), whereby the 5‐year overall survival for stages 1, 2 and 3 were 82%, 62% and 40% years (Palumbo et al , ).…”
Section: Prognostic Staging System In Al Amyloidosismentioning
confidence: 70%